The impact of sovereign credit ratings on foreign exchange rate returns in Africa - Savadye, Laswet (Graduate School of Business (GSB), 2021)
This study investigates the impact of sovereign credit ratings on foreign exchange rate returns for a sample of 27 African countries over the period 2003–2018 to examine the response of the exchange rates around the time of sovereign rating announcements. The data consist of longterm foreign currency sovereign ratings, outlooks, watch lists and daily exchange rates. The study applies a combination of an event study methodology using both univariate and multivariate analyses and the Granger causality tests in a panel framework as well as impulse response tests. The results suggest that, in Africa, exchange rates do not react significantly to changes in sovereign credit rating announcements. No significant evidence of contagion was found. It is thus implied that foreign exchange rates do not react significantly to new information from credit rating agencies which shows a disjoint between macro-economic fundamental performance and financial markets. African countries are encouraged to focus on stabilising their currencies, as well as attending to macro-economic fundamentals that will result in improved credit ratings.